The Effect of Ownership Structures on Audit Fees of Listed Firms in Ghana - Alhassan Musah; Bismark Okyere; Eric Agyapong Boakye (Journal of Accounting and Investment, 2021)
Research aims: The study examined the effect of ownership structures on audit fees of listed firms in Ghana. The study used four indicators to measure ownership structure: managerial ownership, foreign ownership, government ownership, and substantial (block) ownership.Design/Methodology/Approach: The study sampled 21 listed non-financial firms over ten years, covering the period 2010 to 2019. The study also relied on secondary data extracted from the financial statement of these listed firms. Data were analyzed using descriptive statistics, correlation analysis, and panel regression analysis.Research findings: The study results showed a positive and significant association between foreign ownership and audit fees in Ghana. The study further found a positive and significant relationship between block ownership and audit fees. The results, however, uncovered an insignificant association between government ownership and audit fees. Furthermore, the study reported a positive coefficient between block ownership and audit fees, and the relationship was statistically significant.Theoretical contribution/Originality: The study is among very few studies that have examined ownership structures such as foreign ownership, managerial ownership, government ownership, and block ownership on audit fees in a developing country context and Ghana.Practitioner/Policy implication: This study found that the higher agency conflict through ownership structures will give rise to the higher audit fees paid to external auditors, which managers and auditors should consider in future assignments.Research limitation/implication: The study is limited by geographical area (Ghana), and as such future studies can conduct cross-country analysis of ownership structures on audit fees.